2012
DOI: 10.1097/prs.0b013e3182450b47
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Adipogenesis by Lymphatic Fluid Stasis

Abstract: Background Although fat deposition is a defining clinical characteristic of lymphedema, the cellular mechanisms that regulate this response remain unknown. The goal of this study was to determine how lymphatic fluid stasis regulates adipogenic gene activation and fat deposition. Methods Adult female mice underwent tail lymphatic ablation and sacrifice at 1, 3, or 6 weeks post-operatively (n=8/group). Samples were analyzed by immunohistochemistry and western blot. An alternative group of mice underwent axilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(53 citation statements)
references
References 18 publications
(30 reference statements)
2
51
0
Order By: Relevance
“…Recent studies using a novel murine model of lymphedema have implicated lymphatic fluid stasis and inflammation in the pathophysiology of adipogenesis. 38,39 Similarly, abnormalities in the Prox1 pathway, which is critical for lymphatic vasculature, have been associated with increased adipose tissue accumulation and adult-onset obesity. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using a novel murine model of lymphedema have implicated lymphatic fluid stasis and inflammation in the pathophysiology of adipogenesis. 38,39 Similarly, abnormalities in the Prox1 pathway, which is critical for lymphatic vasculature, have been associated with increased adipose tissue accumulation and adult-onset obesity. 40 …”
Section: Discussionmentioning
confidence: 99%
“…This disease affects millions of persons worldwide and most commonly involves swelling of the extremities, tissue fibrosis, susceptibility to infections, and accumulation of subcutaneous fat (Aschen et al, 2012; Brorson, 2016; Rockson, 2001; Witte et al, 2001). Complications of lymphedema include psychosocial morbidity, infection, functional disability, skin changes, and malignant transformation (Greene and Maclellan, 2013).…”
Section: Lymphatic Vascular Systemmentioning
confidence: 99%
“…At the same time, excess FFAs in the enlarged adipocytes would facilitate endothelial damage, which also contributes to lymphatic function defects. At least in mice, any minor injury to the lymphatic system activates adipose differentiation genes and leads to adipose tissue hypertrophy and proliferation (Aschen et al, 2012). Finally, and as the lymphatic system is a physiologic regulator of inflammation and immune responses, obesity-induced lymphatic dysfunction may act in a feed-forward manner to amplify the pathological consequences of obesity.…”
Section: A Bi-directional Cross-talk Between the Lymphatic Vasculaturmentioning
confidence: 99%
“…Lymphedema can be the consequence of a genetic defect (primary lymphedema) or injury to the lymphatic vasculature (secondary lymphedema) as a result of surgery, infection, or radiation therapy (13). The main features of lymphedema include swelling of the extremities, tissue fibrosis, susceptibility to infections, and accumulation of subcutaneous fat (1, 2, 4). Recent data support the view that impaired lymph drainage also causes changes in the immune and inflammatory responses, dysregulation of body fluid homeostasis, disturbances of lipid metabolism and transport, and alterations in the extent of cancer metastasis and obesity (57).…”
Section: Introductionmentioning
confidence: 99%
“…Despite some well-established connections between lymphatic function and lipid absorption and transport, the role of the lymphatic vasculature in adipose metabolism has only recently been recognized (12, 13), and it is known that chronic lymphedema leads to adipose tissue accumulation in the affected area (14, 15). Surgeons have indicated that, in lymphedema, the excess fluid is accompanied by “wet fat” (16) and that “lymphedema is clinically characterized by progressive fat deposition and tissue fibrosis” (4). Edema has also been associated with marked lipid accumulation.…”
Section: Introductionmentioning
confidence: 99%